2015
DOI: 10.1111/asj.12449
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lactic acid bacterial starter culture and chemical additives on wilted rice straw silage

Abstract: Lactic acid bacteria (LAB) are suitable for rice straw silage fermentation, but have been studied rarely, and rice straw as raw material for ensiling is difficult because of its disadvantages, such as low nutrition for microbial activities and low abundances of natural populations of LAB. So we investigated the effect of application of LAB and chemical additives on the fermentation quality and microbial community of wilted rice straw silage. Treatment with chemical additives increased the concentrations of cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…Lower diversity in LAB treated silages as compared to untreated silages were also reported in rice straw and corn ensiling (Wang et al, 2016; Keshri et al, 2018), which can be attributed to the inhibitory effect of the LAB population upon the multiplication of other microbes, before the development of the indigenous LAB population (Keshri et al, 2018). A decrease in bacterial diversity upon ensiling was also observed in other crop silages and ensiling times using NGS (Eikmeyer et al, 2013; Kasmaei et al, 2016; Ni et al, 2017; Romero et al, 2017; Duniere et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Lower diversity in LAB treated silages as compared to untreated silages were also reported in rice straw and corn ensiling (Wang et al, 2016; Keshri et al, 2018), which can be attributed to the inhibitory effect of the LAB population upon the multiplication of other microbes, before the development of the indigenous LAB population (Keshri et al, 2018). A decrease in bacterial diversity upon ensiling was also observed in other crop silages and ensiling times using NGS (Eikmeyer et al, 2013; Kasmaei et al, 2016; Ni et al, 2017; Romero et al, 2017; Duniere et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…Mcdonald et al [15] reported that about 80% were found as leuconostocs, and lactobacilli were the least common on silage materials. Wang et al [17] reported that some lactobacilli (such as Lactobacillus helveticus ) cannot live well on the surface of rice straw. These findings may explain the low LA contents in M and C silage.…”
Section: Discussionmentioning
confidence: 99%
“…However, straw is low quality roughage characterized by high crude fiber, low protein contents and digestibility. Recently, it is possible to use chemicals (Wang et al 2016), enzymes (Ni et al 2014) and inoculants (Zhang et al 2016a) containing lactic acid bacteria (LAB) to overcome these problems in order to enhance the preservation of straw silage. Of these techniques, inoculants are more advantageous in that they are safe, noncorrosive to farm machinery, do not pollute the environment, and are less costly than enzyme preparation (Weinberg and Muck 1996).…”
Section: Introductionmentioning
confidence: 99%